2016
DOI: 10.5935/0103-5053.20160149
|View full text |Cite
|
Sign up to set email alerts
|

The GenusPsychotria: Phytochemistry, Chemotaxonomy, Ethnopharmacology and Biological Properties

Abstract: Psychotria genus (Rubiaceae) is featured into the angiosperm, being the most speciose genus comprising approximately 1600 species. The available references demonstrate that Psychotria has several uses on traditional medicine including spiritual and cultural purposes, and presents great potential on pharmacological properties, especially the one related to neurodegenerative diseases. Despite its wide biological properties, this genus has shown complex phylogenetic analysis due to lack of chemotaxonomic informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
1
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 64 publications
0
35
1
3
Order By: Relevance
“…The antioxidant activity was investigated in aqueous methanol extract of leaves of Prunus avium , Prunus persica , Prunus domestica , Olea europea , Pirus communis , Pirus malus , Pistachia verra , and Castanea sativa and it was found that the leaves of chestnut and plum have the greatest antioxidant activity while lowest was observed in peach, olive and cherry [ 25 ]. Psychotria genus is cited as possessing highl anti-oxidant activity which might be due to the presence of monoterpene alkaloids psycolatine, brachicerine isolated from P. brachiceras and P. umbellata [ 2 ]. Chokeberry and elderberry were also indicated as good sources of antioxidant [ 36 ].…”
Section: Fruits Species and Their Medicinal Properties: An Updatementioning
confidence: 99%
See 3 more Smart Citations
“…The antioxidant activity was investigated in aqueous methanol extract of leaves of Prunus avium , Prunus persica , Prunus domestica , Olea europea , Pirus communis , Pirus malus , Pistachia verra , and Castanea sativa and it was found that the leaves of chestnut and plum have the greatest antioxidant activity while lowest was observed in peach, olive and cherry [ 25 ]. Psychotria genus is cited as possessing highl anti-oxidant activity which might be due to the presence of monoterpene alkaloids psycolatine, brachicerine isolated from P. brachiceras and P. umbellata [ 2 ]. Chokeberry and elderberry were also indicated as good sources of antioxidant [ 36 ].…”
Section: Fruits Species and Their Medicinal Properties: An Updatementioning
confidence: 99%
“…Leaf extracts of Eugenia uniflora proved efficient against Leishmania amazonensis [ 22 ]. Antiviral activity was reported with P. ipecacuanha alkaloids and emetine was found to inhibit the HIV virus, while P. serpens extract suppressed herpes simplex [ 2 ]. Syzygium cumini fruit juice extract possessed antibacterial and gastroprotective activity [ 28 ].…”
Section: Fruits Species and Their Medicinal Properties: An Updatementioning
confidence: 99%
See 2 more Smart Citations
“…Among the secondary metabolites described from the genus Psychotria, the alkaloids stand out (Calixto et al, 2016;Yang et al, 2016;Carvalho Junior et al, 2017). To exemplify the importance of alkaloids in Psychotria spp., it is worth mentioning that this class of secondary metabolites has chemotaxonomic value in the genus (Lopes et al, 2004).…”
Section: Discussionmentioning
confidence: 99%